A Filosofia no Ensino Médio e suas Representações Sociais - Barbosa, Claudio Luis de Alvarenga (2005)
Leaving of some verifications empiric initials, we had opportunity to notice that the teacher that teaches philosophy in the medium teaching has difficulty to get to wake up in their students the interest for the study of that discipline. In spite of usually to happen in just a series of that teaching level, the philosophy gets, in that I tan space of time, to generate a certain discomfort among the student body that frequents those classes. Starting from that verification, we sensed that the one that seems be in question it is the elaboration of social representations of the philosophy in the medium teaching. In that way, to inquire into the philosophy in the medium teaching using contributions of the Theory of Social Representation (MOSCOVICI, 2003, 2001, 1978), we intended to identify concepts and images formed by students and teachers of the medium teaching, and their pedagogic coordinators, while subjects that can offer their perceptions. To the we try to obtain, through the subject of the process, those social representations, our interest is to think about philosophy teaching and their education senses, discussing which kind of the philosophy that we intend to teach in the medium teaching and for something to do it. With those data, we believed to bring contributions for teachers that are in charge of of the philosophy in the medium teaching, in the interest that discipline get to understand the importance of that discipline as essential factor to the student's formation. By the way, we can, also, to demonstrate the importance of the presence of that discipline in the school curriculum.